A market research paper about Papa John’s Pizza - Go, Michael C. (Animo Repository, 2012)
The study is an evaluation of Papa John's and its competitors in the Pizza market. The study started with the background of the study by looking first at the food industry and what drives the demand for food. The study has found that pizza is a favourite snack time in the Philippines and it is an indulgent item that Filipinos would like to eat occasionally. Furthermore the study wanted to know the preferences of Filipinos when eating or buying pizza at the same time make a competitive analysis to see the similarities and differences between Papa John's and its competitors. The study has also included term and definitions in the food service sector and pizza market that will further enhance the contents of the study. The review of related literature includes previous research and studies that contributed to the initial findings of the study in the previous chapter. The methodology section shows how the study was conducted, sources of primary and secondary data, and the statistical tests used to verify the findings of the survey. A survey was conducted to see the preferences of Filipinos when it comes to pizza. In the conclusions part, the study findings in the survey and competitive analysis were used to confirm initial data, consequently making the recommendations that Papa John's can use to evaluate their situation in the pizza market in the Philippines at the same time apply the findings of the study which they can use ifor further research and making their marketing plan.